Aspekty funkcjonowania innowacyjnych przedsiębiorstw na przykładzie Polski Wschodniej/Aspects of the operation of innovative companies on the example of Eastern Poland - Iwona Koza (Language, Culture, Politics)
Innovation is the subject of numerous studies in which researchers look for its conditions, causes and effects. The innovation process begins even before the commencement of scientific research in the enterprise, usually at the stage of creating an idea, and ends with the implementation of innovation and its dissemination. It is worth constructing a wide range of indicators which refer to the condition or determinants responsible for the functioning of innovative companies, and also for the discussion of such issues as entrepreneurship, technological development, and diversity. Particularly interesting may be a detailed specification of the above-mentioned aspects in relation to Eastern Poland - the region with unfavourable conditions for business development, because of the underdeveloped economic base, as well as deficiencies in the development of communication, human resources, and economic as well as local market infrastructures.